Ultrasonic chemical sensor for detection of aliphatic and aromatic hydrocarbons in air - Balcerzak, Andrzej; Zhavnerko, Genady (Archives of Acoustics, 2007)
The reaction of the organic monomolecular Langmuir–Blodgett layer, deposited on the sensor delay line using surface acoustic wave, on the presence of vapors of some aliphatic and aromatic hydrocarbons in air has been investigated. The chemical composition of this layer is an equimolar mixture of 5-[[1,3-dioxo-3- [4- (1-oxooctadecyl) phenyl] propyl] amino] – 1,3 – benzenedicarboxylic acid (DA) and cetylamine (CA). Time of sensor reaction is less than 2 seconds. Decrease of the differential frequency after contact with the vapor-air mixture and decrease of this frequency in time are different for various hydrocarbons; a length of the chain is important for aliphatic hydrocarbons and a presence or not of side chains – for aromatic ones. The reaction of the sensor on the hydrocarbon vapors in air is reversible.